Microstructure effect in the coupling reactions of polymeric organolithium compounds using chlorosilanes - Cho, JC; Kim, KH; Kim, KU; Kwak, S; Kim, J; Jo, WH; Chun, MS; Lee, CH; Yeo, JK; Quirk, RP (WILEY-BLACKWELL, 1998)
The most important variable affecting the yield in the coupling reactions of polymeric organolithium compounds with chlorosilane compounds has been investigated through size-exclusion chromatographic (SEC) analysis. The coupling reaction of poly(styryl)lithium with dichlorodimethylsilane as a silane-coupling agent provided 44 wt % of the coupling yield. The coupling yield, depending on the chain end reactivity of active polymers, was not greatly affected. The addition of a Lewis base such as N,N,N',N'-tetramethylethylenediamine (TMEDA) even after complete polymerization of the dienes in hydrocarbon seems to affect the coupling reaction, resulting in decreasing the yield. The 1,2- or 3,4-enchain contents in the polydiene backbones affected the reduction of the linking efficiency in the coupling of the poly(dienyl)lithiums with chlorosilanes as the linking agent. The linking yields of the active polymers including over 75 mol % of 1,2- or 3,4-enchainment on the polydiene segment were below 20 wt %. The linking yields exhibited a dependence not only on the steric requirement of the chain end, but also the microstructure of the polydiene segment. (C) 1998 John Wiley & Sons, Inc.